Η-Approximation Method for Non-convex Multiobjective Variational Problems. (2nd September 2017) - Antczak, Tadeusz; Michalak, Anna
ABSTRACT: In this paper, we use the η -approximation method for a class of non-convex multiobjective variational problems with invex functionals. In this approach, for the considered multiobjective variational problem, the associated η -approximated multiobjective variational problem is constructed at the given feasible solution. The equivalence between (weakly) eﬃcient solutions in the original multiobjective variational problem and its associated η -approximated multiobjective variational problem is established under invexity hypotheses.